Unusual Presentation of Jimson's Weed Toxicity- A Case Report - Chakraborty, Arpita; Bakkannavar , Shankar M; Hebbar , Shrikiran A (Journal of Indian Academy of Forensic Medicine, 2020)
The characteristic features of toxicity help clinician diagnose the case in time and start treatment immediately. However, in many  instances, unusual presentations of symptoms and signs not only cause difficulty in diagnosis the condition but also cause delay in  starting effective treatment. In such cases there is always a threat of fatality. Knowledge about such unusual presentations is essential  in managing such cases. We present one such unusual presentation in a case of Jimson's weed poisoning case. Timely diagnosis of  case through recognizing unusual presentation saved the life of a boy.
Keywords: Toxicity; Unusual presentations; Jimson's weed